Development of self-regulated learning skills in mathematics in lower secondary school in Sweden - Samuelsson, Joakim (NOMAD Nordic Studies in Mathematics Education, 2011)
In this study, the development of 219 students’ self-regulated learning skills in lower secondary school across ability groups were investigated and related to measures of students’ performance in mathematics. Self-regulated learning skills were assessed with a questionnaire originally designed and used in PISA 2003. Pre-testing was performed during the first two weeks in school in seventh grade. The first post-test was performed after one term in eighth grade, in January 2008. The second post-test was performed during the last two weeks in grade 9, in June 2009. All testing was performed by the class teacher. However, the result states that internal motivation, instrumental motivation as well as self-concept decline across year in lower secondary school. The development of interest and enjoyment of mathematics, self-concept in mathematics and anxiety in mathematics was similar in each ability group. No interaction effects across groups were significant in the study. This study highlights the importance of taking affective factors into account in discussions about the results of mathematics teaching and learning. The strong correlation between affective factors and achievement in mathematics helps us to identify some weaknesses in the Swedish education system.